Self-Harm Thoughts Postpartum as a Marker for Long-Term Morbidity - Stavros I. Iliadis; Alkistis Skalkidou; Hanna Ranstrand; Marios K. Georgakis; Marios K. Georgakis; Cathrine Axfors; Fotios C. Papadopoulos (Frontiers Media S.A., 2018)
IntroductionPostpartum depression predisposes to maternal affective and somatic disorders. It is important to identify which women are at an increased risk of subsequent morbidity and would benefit from an intensified follow-up. Self-harm thoughts (SHTs), with or without other depressive symptomatology, might have prognostic value for maternal health beyond the postpartum period.AimThis study is to investigate the somatic and psychiatric morbidity of postpartum women with SHTs, with or without other depressive symptoms, over a 7-year follow-up period.Materials and methodsThe subjects for this study are derived from a population-based Swedish cohort of women who gave birth at Uppsala University Hospital (May 2006-June 2007) and who answered the Edinburgh Postnatal Depression Scale (EPDS) at 5 days, 6 weeks, and 6 months postpartum. Three groups were included: women reporting SHTs (SHT group, n = 107) on item 10 of the EPDS; women reporting depressive symptoms, i.e., EPDS ≥ 12 at 6 weeks and/or 6 months postpartum, without SHTs (DEP group, n = 94); and randomly selected controls screening negatively for postpartum depression (CTL group, n = 104). The number of diagnostic codes for somatic and psychiatric morbidity according to the International Statistical Classification of Diseases and Related Health Problems system, and the number of medical interventions were retrieved from medical records over 7 years following childbirth and were used as the outcome measures, together with any prescription of antidepressants and sick leave during the follow-up.ResultsThe SHT group had the highest psychiatric morbidity of all groups and more somatic morbidity than controls. Affective disorders were more common in the SHT and the DEP groups compared with controls, as well as antidepressant prescriptions and sick leave. One-fifth of women with SHTs did not screen positive for depressive symptoms; nevertheless, they had more somatic and psychiatric morbidity than the control group.ConclusionWomen reporting thoughts of self-harm in the postpartum period are at an increased risk of somatic and psychiatric morbidity during a follow-up of 7 years after delivery, and this increased risk may not be fully attributed to depressive symptoms. Results underline the importance of screening for self-harm symptoms postpartum and point to a need for individualized follow-up.